Human HepaRG liver spheroids: cold storage protocol and study on pyridinium oxime-induced hepatotoxicity in vitro. (5th January 2023) - Horn, Gabriele; Kranawetvogl, Tamara; John, Harald; Weigel, Carlotta; Rauen, Ursula; Worek, Franz; Wille, Timo
Abstract: Oximes play an essential role in the therapy of organophosphorus compound (OP) poisoning by reactivating inhibited acetylcholinesterase. Impairment of liver function was observed in OP poisoning and associated with obidoxime treatment by some reports. In this study human three-dimensional HepaRG spheroids were used as complex in vitro model to investigate oxime-induced liver toxicity. In this context, cold storage of liver spheroids at 4 °C in standard culture medium and in optimized tissue preservation solutions of up to 72 h was assessed. Cold storage in standard culture medium resulted in a complete loss of viability whereas an optimized tissue preservation solution preserved viability. Separately from that liver spheroids were exposed to the four oximes pralidoxime, obidoxime, HI-6, MMB-4 and cytotoxicity (effective concentration, EC50 ) was determined with an ATP-based assay at several time points. The release of aspartate aminotransferase (AST), alanine aminotransferase (ALT) and albumin secretion was measured in supernatants. The same parameters were assessed with diclofenac as positive hepatotoxic control and with the OP pesticides malathion and malaoxon alone or in the presence of obidoxime. All individual tested oximes and OP showed a low cytotoxicity with effective concentrations mostly >2, 000 μM. In contrast, the exposure to malaoxon in the presence of 1, 000 μM obidoxime resulted in a marked decrease of viability and an increased release of AST indicating risk of liver injury only if oxime antidotes are strongly overdosed. Highlights: Cold storage of HepaRG spheroids was optimized with a tissue preservation solution. HepaRG spheroids were exposed to four oximes resulting in low cytotoxicity. The combination of malaoxon with obidoxime resulted in marked decrease of viability. Liver injury after OP poisoning may be provoked only by severe oxime overdosing.